Gamification of Learning in the Perspective of Constructivism Philosophy Lev Vygotsky - Rohman, Darus; Fauziati, Endang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The industrial revolution encouraged teachers to change traditional learning systems into modern ones. The media used in learning certainly changes according to the characteristics of students. One approach that is suitable for 21st century education is through gamification. Gamification in learning support students in understanding the material in an easier and funnier way. The aim of this study is to describe gamification learning media in the perspective of Vygotsky's constructivism philosophy. This study uses library research based on library data, namely examining the learning media of gamification and Vygotsky's philosophy of constructivism which is carried out using literature in the form of rules that support in analyzing research topics. The approach that is used in this research is descriptive qualitative approach. In this study, exploration and providing arguments related to gamification learning media are carried out with the analysis of Vygotsky's constructivism philosophy. The result of this study examine that gamification learning media can be viewed from the perspective of constructivism philosophy according to the three components of Lev Vygotsky's theory. The three components of Vygotsky's theory are Zoneiof Proximal Development (ZPD), Scaffolding andiMore Knowledgeable Others (MKO). This research is hopped to become a solution to the problem of low learning motivation of students and help students to solve their own problems, thus forming the character of students who think critically.